We know that angles ZC and ZD are vertical angles, this means they are equivalent by definition.
![m\angle ZC=m\angle ZD](https://img.qammunity.org/2023/formulas/mathematics/high-school/7g6zmthufg723zcuilxmri5ohp72n6xk39.png)
Replacing the given expressions-
![-2.1+90=x-30](https://img.qammunity.org/2023/formulas/mathematics/high-school/jcbsvqqh818zj8u68g4tngpya0h2puwqd9.png)
First, we have to reduce like terms
![87.9=x-30](https://img.qammunity.org/2023/formulas/mathematics/high-school/3pithzifer04cfeted1gn3jt36vg9kun04.png)
Now, we sum 30 on each side
![\begin{gathered} 87.9+30=x-30+30 \\ 117.9=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nx9txjifack1xlv8gunrqpuq2c5u23fu65.png)
We use this value to find angle ZD.
![m\angle ZD=x-30=117.9-30=87.9](https://img.qammunity.org/2023/formulas/mathematics/high-school/lzrm4vkgj44a1kv34t6y5vy75b1ei7fn0i.png)
Therefore, angle ZD is equal to 87.9°